Comparative Analysis of Cognitive Characteristics of Young Adolescents with Artistic and Intellectual Giftedness - Donii E.I; Shumakova N.B (Moscow State University of Psychology and Education, 2020)
The work is aimed at identifying specific manifestations of creativity and basic cognitive characteristics in young adolescents with artistic and intellectual giftedness. The relevance of the study is due to lack of study of the issue of cognitive manifestations of different types of giftedness in early adolescence, in which the issue of specialization of education is often resolved. The study involved 54 intellectually gifted adolescents (M = 11.4 years old) and 32 artistically gifted peers (M = 11.2 years old). The study used the following methods: a computerize d battery of test tasks for studying bas ic cognitive characteristics ("number sense", visua l working memory and information processing speed), "Raven's Progressive Matrixes", "Verbally-figura l creativity test", drawing tests of Urban and "Horizon Line ". The results confirm the hypothesis about the specificity of creativity in younger adolescents with different types of giftedness (intellectual and artistic). Intellectually gifted younger adolescents show higher rates of divergent verbal creativity compared to their artistically gifted peers; and artistically gifted younger adolescents surpass their intellectually gifted peers in terms of picturesque (figurative) creativity and are distinguished by their highquality originality, revealing a high emotional expressiveness and creative approach to the implementation of the plan. No statistically significant intergroup differences in the basic indicators of cognitive development and general intelligence were found, although artistically gifted adolescents better than their intellectually gifted peers compare asymmetrically expressed amounts ("number sense"), but they are inferior in terms of information processing speed.